A Review of Recently Discovered Remains of the Pleistocene Branchiopods (Anostraca, Notostraca) from NE Siberia and Arctic Canada - D. Christopher Rogers; Anton A. Zharov; Anna N. Neretina; Svetlana A. Kuzmina; Alexey A. Kotov (Water, 2021)
In this study, we examine, identify, and discuss fossil remains of large branchiopod crustaceans collected from six sites across the Beringian region (north-eastern Asia and north-western North America). Eggs and mandibles from Anostraca and Notostraca, as well as a notostracan telson fragment and a possible notostracan second maxilla, were collected from both paleosediment samples and also from large mammal hair. The remains of large branchiopods and other species that are limited to seasonally astatic aquatic habitats (temporary wetlands) could be useful indicator organisms of paleoecological conditions. Different recent large branchiopod species have very different ecological preferences, with each species limited to specific geochemical component tolerance ranges regarding various salinity, cation, and gypsum concentrations. Our purpose is to bring the potential usefulness of these common fossil organisms to the attention of paleoecologists.